CP8 Biocommunicators for parasitic weed control: honeypot strategy - Francisco Antonio; Zorrilla, Jesús G.; Rial, Carlos; Rodríguez-Mejías, Francisco J.; Varela, Rosa M.; González Molinillo, José María (Revista Productos Naturales, 2025)
Parasitic weeds pose a significant threat to agricultural productivity, necessitating the development of sustainable control methods. Traditional herbicides have led to the emergence of resistant weed varieties, underscoring the urgent need for environmentally friendly and effective alternatives.
Keywords: Parasitic weeds; honeypot strategy; strigolactones; organic synthesis; encapsulations